Phylogeny and Revision of Toechorychus Townes (Hymenoptera, Ichneumonidae, Cryptinae), with descriptions of thirty-five new species - Tedesco, Anazélia M.; Aguiar, Alexandre P. (Zootaxa, 2013)
The Neotropical Toechorychus Townes is revised, cladistically defined, and diagnosed. A total of 40 species are recognized, 35 of which are described as new: T. amapaeus Tedesco, sp. nov., T. amazonensis Tedesco, sp. nov., T. barticus Tedesco, sp. nov., T. benius Tedesco, sp. nov., T. bombuscarus Tedesco, sp. nov., T. calius Tedesco, sp. nov., T. callangus Tedesco, sp. nov., T. catarinus Tedesco, sp. nov., T. coaracius Tedesco, sp. nov., T. darienus Tedesco, sp. nov., T. fluminensis Tedesco, sp. nov., T. guarapuavus Tedesco, sp. nov., T. heredius Tedesco, sp. nov., T. itapuensis Tedesco, sp. nov., T. jatainus Tedesco, sp. nov., T. kawus Tedesco, sp. nov., T. linaresius Tedesco, sp. nov., T. marcapatus Tedesco, sp. nov., T. marowijnus Tedesco, sp. nov., T. martinus Tedesco, sp. nov., T. melgassus Tedesco, sp. nov., T. morelus Tedesco, sp. nov., T. napus Tedesco, sp. nov., T. nourageus Tedesco, sp. nov., T. ondensis Tedesco, sp. nov., T. paramaribus Tedesco, sp. nov., T. pirrus Tedesco, sp. nov., T. sinopus Tedesco, sp. nov., T. surinamus Tedesco, sp. nov., T. taperinus Tedesco, sp. nov., T. teutonius Tedesco, sp. nov., T. tumazulus Tedesco, sp. nov., T. vilhenus Tedesco, sp. nov., T. vinhaticus Tedesco, sp. nov., T. zulius Tedesco, sp. nov. The other valid species are T. abactus (Cresson), T. albimaculatus (Taschenberg), T. brevicaudis (Szépligeti), T. cassunungae (Brauns), and T. stramineus (Taschenberg). Toechorychus can be recognized by the epicnemial carina usually not reaching more than 0.3 of the distance to subtegular ridge; dorsal valve of ovipositor with a subapical V-shaped sulcus; ovipositor with a subapical constriction; ovipositor sheath about 0.1 as long as hind tibia; and dorsal margin of pronotum swollen. A key and descriptions, including photographic illustrations and distribution maps, are provided to all valid species; a cladistic analysis of the genus is also performed. Seventy three new characters are proposed for the analysis of Cryptinae phylogeny. Toechorychus was recovered as a monophyletic group supported by 7–17 synapomorphies, closely related to Lymeon Förster and Acerastes Cushman. Two new synapomorphies are discovered for Toechorychus, a subapical V-shaped sulcus at the dorsal valve of the ovipositor, and a subapical constriction of the ovipositor present basad of the apical teeth of the ventral valve. Published host records were compiled and three new records are provided as follows: T. albimaculatus is a parasitoid of Mischocyttarus drewseni (Saussure) (Vespidae, Polistinae); T. stramineus is a parasitoid of M. basimacula (Cameron) and T. heredius sp. nov. is a parasitoid of M. collarellus Richards. A neotype is designated for T. cassunungae.